EFFECTIVE TAX RATE PADA BUMN: APAKAH FIRM GROWTH, EARNINGS MANAGEMENT, DAN GOVERNMENT OWNERSHIP RELEVAN? - Fadhia Dwi Aulina; Intan Kurnia Permatasari (Jurnal Akuntansi Kompetif, 2026)
Tax is a primary component of state revenue. However, the optimization of tax revenue in Indonesia, particularly Corporate Income Tax, still faces complex dynamics as reflected in fluctuations in revenue over recent years. This indicates that the effectiveness of tax management has not been fully stable and is still influenced by various factors. Therefore, this study aims to analyze the effect of firm growth, earnings management, and government ownership on the ETR. The population consists of 27 state-owned enterprises listed on the Indonesia Stock Exchange during 2020–2024, with a sample of 13 companies selected using purposive sampling. The method employs a quantitative approach with multiple linear regression analysis using SPSS. The results show that firm growth and earnings management have a significant effect on ETR, while government ownership does not. These findings indicate that internal company dynamics play more dominant role than ownership structure in determining tax management effectiveness.